Aristotle Poetics - Aristotle. (Mnemosyne, Supplements, 2012)
This important new editio maior of Aristotle's Poetics , based on all the primary sources, is a major contribution to scholarship. The introductory chapters provide important new insights about the transmission of the text to the present day and especially the significance of the Syro-Arabic tradition. The Greek text is accompanied by a detailed critical apparatus as well as Notes to the Text; in addition there is a Graeco-Arabic critical apparatus and commentary. An Index of Greek Words, Indices, and a Bibliography complement the work. This publication will be an indispensable tool for all Aristotelian scholars, historians of Greek literature and criticism, and specialists of the transmission and reception of classical works.